2017
DOI: 10.1111/cdev.12722
|View full text |Cite
|
Sign up to set email alerts
|

Peer Groups as a Context for School Misconduct: The Moderating Role of Group Interactional Style

Abstract: Peer group interactional style was examined as a moderator of the relation between peer group school misconduct and group members' school misconduct. Participants were 705 students (M = 11.59 years, SD = 1.37) in 148 peer groups. Children reported on their school misconduct in fall and spring. In the winter, group members were observed in a limited-resource task and a group conversation task, and negative and positive group interactional styles were assessed. Multilevel modeling indicated that membership in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
2
2
0
Order By: Relevance
“…With respect to our first hypothesis on the effect of peer influence on risk taking, negative risk encouragement by peers was related to more risk taking than no peer influence. This is in line with three lines of evidence showing that social exclusion and peers' negative interactional styles are related to reputation management, stress causing decreased inhibition, and risk taking (Bjork and Pardini 2015;Blakemore 2018;Brechwald and Prinstein 2011;De Houwer and Tibboel 2010;Ellis et al 2018;Gunther Moor et al 2014;Nesdale and Lambert 2008). Adolescents did not demonstrate more risk taking when peers positively encouraged risk taking than without peer influence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With respect to our first hypothesis on the effect of peer influence on risk taking, negative risk encouragement by peers was related to more risk taking than no peer influence. This is in line with three lines of evidence showing that social exclusion and peers' negative interactional styles are related to reputation management, stress causing decreased inhibition, and risk taking (Bjork and Pardini 2015;Blakemore 2018;Brechwald and Prinstein 2011;De Houwer and Tibboel 2010;Ellis et al 2018;Gunther Moor et al 2014;Nesdale and Lambert 2008). Adolescents did not demonstrate more risk taking when peers positively encouraged risk taking than without peer influence.…”
Section: Discussionsupporting
confidence: 89%
“…This is also in line with the need-to-belong theory predicting that social exclusion leads to decreased self-regulation (Baumeister et al 2005;DeWall et al 2008;Stenseng et al 2015). Finally, longitudinal studies confirm that a negative interactional style between adolescents (i.e., negative laughter and coercive statements) predicts adolescents' school misconduct and risk taking (Ellis et al 2018).…”
Section: Sex Differences In Susceptibility To Peer Influencesupporting
confidence: 85%
“…A recent study examining the impact of the pandemic, and its related restrictions, on the emotional health of Canadian adolescents found that concerns related to COVID-19, difficulties with online learning and increased family conflict were associated with higher levels of depression and anxiety, whereas feeling socially connected during the COVID-19 lockdown protected the adolescents against poor mental health (46). Given that different types of trauma exposure (e.g., interpersonal or non-interpersonal) probably have differential effects on adolescent cognition and traumatic-and stress-related symptoms, as well as PTSD onset (47)(48)(49)(50), and that adolescents rely on peer connections and relationships for their emotional support and social development (51), it is argued that social isolation and social distancing may be an important adversity factor for developing brain systems engaged in social and emotional processes (44). Although it may take years and numerus research studies to fully understand the sequelae of the COVID-19 pandemic during different developmental stages, available data have consistently demonstrated an association of several COVID-19-related stressors with mental health outcomes.…”
Section: Covid-19 Trauma and Post-traumatic Stress Disorder In Children And Adolescentsmentioning
confidence: 99%
“…Adolescents also confirm and encourage each other in deviance through deviancy training (Dishion et al, 1996). Moreover, peer group influence on adolescents' misconduct is intensified if peers within a group engage in negative laughter and endorse a coercive interaction style (Ellis et al, 2018).…”
Section: How Peers Influence and Select Each Othermentioning
confidence: 99%